Adult smokers' receptivity to a television advert for electronic nicotine delivery systems. Issue 2 (3rd October 2013) - Kim, Annice E; Lee, Youn Ok; Shafer, Paul; Nonnemaker, James; Makarenko, Olga
Abstract : Objective: The aim of the present work was to examine adult smokers' awareness of and receptivity to an electronic nicotine delivery system (ENDS) television advert, and whether viewing the advert influenced urge to smoke and intention to try ENDS. Methods: A television advert for ENDS brand blu eCigs was shown to an online convenience sample of 519 Florida adult smokers. We measured current smokers' awareness of and receptivity to the advert, and whether seeing the advert influenced their thoughts about smoking or quitting, urge to smoke and intention to try ENDS. Results were stratified by prior ENDS use. Results: Approximately 62.3% of current smokers were aware of the advert. Smokers found the advert informative (73.8%), attention grabbing (67.5%) and innovative (64.5%), with prior ENDS users rating the advert more favourably than non-users. Seeing the advert elicited an urge to smoke (mean 42.1, SD=1.9) and thoughts about smoking cigarettes (75.8%) as well as quitting (74.6%). Prior END users were significantly more likely than non-users to report thinking about smoking cigarettes after seeing the advert (P<0.05). Most smokers said ENDS were 'made for people like them' (88.6%) and they would try ENDS in the future (66.0%). Conclusions: Smokers are receptive to ENDS television adverts and report intention to try ENDS after viewing the advert. Future studies should monitor ENDS advertising and examine how exposure to ENDS adverts influences smokers' use of ENDS, dual use with cigarettes and cessation behaviour.